Exploring Community Formation and Coalescence at the Late Fourteenth–Early Fifteenth-Century Tillsonburg Village Site (AfHe-38) - Rebecca Parry (Canadian Journal of Archaeology/Journal canadien d'archéologie, 2019)
The concept of community coalescence involves the aggregation of previously separate social groups into one communal settlement. This has facilitated a greater understanding of Iroquoian community formation during the Late Woodland of southern Ontario. It is explored as the predominant conceptual approach to better understand the formation of the Tillsonburg Village’s (AfHe-38) community plan, however, other processes relating to the contemporaneity of village areas or houses are also considered. The site is located in Tillsonburg, Ontario and dates from the late fourteenth to early fifteenth century (AD 1350–1420). This paper explores the village’s particularly large and dispersed community plan through an intra-site analysis of ceramic vessels and longhouse attributes, as these are considered useful indicators of social, organizational, and temporal processes. Spatial and statistical analyses are used to explore spatial patterning of attributes among their associated contexts. The results suggest that the Tillsonburg occupants were experimenting with formative processes of community coalescence; with groups interacting and living together in one settlement, yet remaining socially and spatially distinct within the larger village community.